Adoption of sustainable low-impact fishing practices is not enough to secure sustainable livelihoods and social wellbeing in small-scale fishing communities. (December 2022) - de la Puente, Santiago; López de la Lama, Rocío; Llerena-Cayo, Camila; Martínez, Benny R.; Rey-Cama, Gonzalo; Christensen, Villy; Rivera-Ch, María; Valdés-Velasquez, Armando
Abstract: Improving small-scale fishers' wellbeing is a core policy objective in efforts to achieve just, equitable and sustainable futures. Nonetheless, fishers' wellbeing is rarely assessed or monitored over time using quantitative indicators. We evaluated the socio-economic performance and evolution of two small-scale fishing communities of northern Peru using the Sustainable Livelihoods Approach. Quantitative indicators were used to characterize fishers financial, human, natural, physical, and social capitals. We also developed a simple, yet novel, composite index to quantify fishers' Unsatisfied Basic Needs. This approach allowed us to grasp changes in the material and relational dimensions of fishers' wellbeing over time. Fishers in these communities had: (i) low human and financial capital assets, (ii) strong social capital assets, and (iii) experienced improvements in their physical capital assets whilst reporting declines in their natural capital assets. Although fishers mainly use highly selective, low-impact fishing methods, their target stocks and incomes are declining. People's wellbeing in these communities was highly vulnerable to external environmental (e.g., El Niño) and economic (e.g., access to markets) drivers as well as poor governance (e.g., weak rule of law, low institutional fit, corruption). Our results suggest that small-scale fishers of these two sites are currently in a social-ecological trap, with many points of entry and few ways out. We discuss potential avenues for escaping the trap and improving their wellbeing based on commonly suggested livelihoods strategies found in the literature. Highlights: The Sustainable Livelihoods Approach was used to assess fisher's wellbeing in Peru. Novel indicators were developed to characterize fishers' capital assets. Small-scale fishers in Peru are caught in a social-ecological trap. Fishers' livelihoods are not sustainable, yet they mostly use selective fishing gears. Improving fishers' wellbeing requires broadening the scope of fisheries research.